Compensation as appreciation for surrender and present all of employee wo/t(s result to belong to centre, divided to financial and non financial. Financial compensation among other things are direct financial, one of its insentive and indirect financial in formed subsidy. Looking for insentive characteristic which is to take directly between employees reward with prestation of work that they reach, therefore insentive giving would be motivating the employee to increase their prestation of works. - Iis Diatin; Popong Nurhayati; Titin Maytani (Buletin Ekonomi Perikanan, 2006)
Compensation as appreciation for surrender and present all of employee wo/t(s result to belong to centre, divided to financial and non financial. Financial compensation among other things are direct financial, one of its insentive and indirect financial in formed subsidy. Looking for insentive characteristic which is to take directly between employees reward with prestation of work that they reach, therefore insentive giving would be motivating the employee to increase their prestation of works.   This research was conducted to analysis of insentive system which used by BPBILAPU Pangandaran, to identificate many factors which decided amount of insentive that employee get and to analysis the using·of insentive system which more efective based of merit system.   Results indicated that insentive system which used by BPBILAPU Pangandaran is group/team insentive system with using profit sharing plan, calculation which the sharing consist of 5% for production team and 10% for aU of employee. Many factors which decided insentive of employee BPBILAPU Pangandaran are human resources, natural resources, capital, environment and market. Insentive system based of merit system consist of individual insentive (piecework, production bonus and pay for knowledge compensation) and group insentive (production sharing plan) more effective to used. Both of them have bigger insentive value than insentive which employee gel Besides of it, insentive value that employee get was established by prestation and productivity of work..